Climate change impact on extreme value and its frequency distribution function in a karst basin, Southwest China. Issue 3 (10th February 2022) - Mo, Chongxun; Song, Xuan; Ruan, Yuli; Lan, Huakun; Lei, Xingbi; Xing, Zhenxiang; Sun, Guikai
Abstract: Studying extreme meteorology and its frequency under climate change is helpful to guide flood and drought control. The original achievements and objective of this study are to further contribute to the literature on how to analyze the impact of climate change on extreme rainfall and extreme temperature more reasonably and comprehensively for a karst basin. The Mann–Kendall method, Heuristic segmentation method, cross-wavelet analysis method, generalized extreme value (GEV) model, and generalized Pareto distribution (GPD) model were applied in this paper. The 55-year (1963–2017) extreme rainfall and temperature data recorded in the Chengbi River Basin were applied. The results show that extreme rainfall showed a downward trend (−0.169 and −8.735 mm/10a), while the trends of extreme temperatures were not obvious (Sen's slope estimate is 0). The mutation points range from 1981 to 2002 and the mutation point of extreme rainfall series is earlier than that of extreme temperatures. Compared with the GEV model, the parameters of the GPD model show a smaller variation before and after climate change, and the extreme meteorology values corresponding to the same recurrence period show a decreasing trend after climate change. The performance of GEV and GPD models after climate change is generally more fit than that before climate change. HIGHLIGHTS: A framework was proposed for further study of the effect of climate change. A trend study to show if climate change impacts the extreme rainfall and temperatures. Figuring out the performance of different models before and after climate change. Graphical Abstract